Phylogenomics and systematics of botryllid ascidians, and implications for the evolution of allorecognition - Nydam, Marie L.; Lemmon, Alan R.; Lemmon, Emily M.; Ziegler, Kevin; Cohen, C. Sarah; Palomino-Alvarez, Lilian A.; Gissi, Carmela (Frontiers in Ecology and Evolution, 2023)
Allorecognition, the ability of an organism to distinguish kin from non-kin, or self from non-self, has been studied extensively in a group of invertebrate chordates, the colonial ascidians called botryllids (Subphylum Tunicata, Class Ascidiacea, Family Styelidae). When two conspecific botryllid colonies come in contact, there are two potential outcomes to an allorecognition reaction: fusion or rejection. The rejection outcome of allorecognition varies by species, and has been classified by type (referred to as R-Type). R-Type is defined according to how far the fusion process progresses before the rejection begins, since the rejection reaction appears as an interference of the fusion process. Here, we map the evolution of R-Types onto an extended and robust phylogeny of the botryllids. In this study, we have reconstructed the largest phylogenomic tree of botryllids, including 97 samples and more than 40 different species, and mapped on it nine of the 13 species for which the R-Type is known. Based on the R-Type known in a single outgroup species (Symplegma reptans), we infer that at least R-Type B and E-like could be ancestral to the Botrylloides/Botryllus group. However, the application of ancestral character state reconstructions does not provide conclusive results since several clades show more than one equiparsimonious R-Type state. Notably, all R-Type A species are clustered together and certainly evolved later than other R-Types. Our phylogenomic tree has been built on 177 nuclear loci and nearly all clades are well supported. Moreover, our phylogenetic analyses also take into account the results of species delimitation analyses based on the mitochondrial COI gene and of careful morphological analyses of the samples. The implementation of this integrated taxonomic approach, combining morphological as well as nuclear and mitochondrial data, has allowed the description of six new species, and the identification of a number of putative unnamed taxa. Thus, our results also demonstrate the existence of an unexplored hidden diversity within botryllids.